Grass production Tifton 85 and nutrient extraction with swine wastewater doses - Vinícius de Oliveira Rezende, Luís César Dias Drumond , André Mundstock Xavier de Carvalho, Regina Maria Quintão Lana, Marcos Vieira de Faria (African Journal of Pig Farming, 2023)
Swine wastewater (SW) is considered as a source of nutrients for agriculture. The quantities and frequencies applied may vary according to the soil class, the nature and composition of the waste, the climatic conditions and the cultivated plant species. Therefore, this study aimed to evaluate the effects of application of five Swine wastewater doses (0, 500, 1000, 2000 and 2500 m³ ha-1 ) in the production of components and grass nutrient extraction Tifton 85 and changes in soil chemical properties after the end of the last application of swine wastewater. To achieve these goals, we evaluated the quantities of extracted nutrients, density and height of the pre-grazing grass, forage accumulation rate and carrying capacity. The experimental design was a randomized block. The production of dry matter was 18159.80 kg ha-1 , and the average height of 85 Tifton was 34.83 cm. The higher carrying capacity, 10 AU ha-1 was obtained with the dosage of 2500 m³ ha-1 . While, the dose of 2000 m³ ha-1 supplied the nutritional needs of Tifton 85 in nitrogen, potassium, calcium, magnesium, copper, iron, zinc and boron. The quantities of extracted nutrients (kg ha-1 ) at grass Tifton 85 grazed were: N = 405.14; P = 57.77; K+ = 387.69; Ca2+ = 77.05; Mg2+ = 49.68; S-SO4-2 = 31.48; B = 0.33; Cu2+ = 0.20; Fe = 2.88; Mn2+ = 4.61; Zn2+ = 2.86. The application of increasing doses of SW promoted a linear increase in grass production components Tifton 85, as well, promoted changes in soil chemical properties and quantities of extracted nutrients.